Validation of the assessment of living with aphasia in Singapore. Issue 9 (2nd September 2017) - Guo, Yiting Emily; Togher, Leanne; Power, Emma; Heard, Rob
ABSTRACT: Background : The Assessment of Living with Aphasia (ALA) is a pictographic, self-report measure of aphasia-related quality of life (QoL). It has yet to be used in the Singapore population or adapted to other languages. Aims : To examine the reliability and validity of the ALA and develop a Mandarin Chinese adaptation, the ALA-C, in the Singapore context. Methods & procedures : Linguistic validation of the ALA was conducted to derive the ALA-C. People with aphasia (PWA) who were at least 6 months post-onset underwent the ALA/ALA-C and a series of reference measures in their dominant language (English/Mandarin). Test–retest reliability was evaluated using intra-class correlations and internal consistency using Cronbach's alpha. Eight reference measures were administered to assess construct validity. Outcomes & results : Sixty-six PWA were recruited to the study. Both the ALA and ALA-C showed excellent internal consistency ( α = 0.97/0.96) and test–retest reliability (intraclass correlation = 0.97/0.98), and acceptable convergent ( r = 0.63–0.83 and 0.70–0.83 respectively) and discriminant ( r = 0.45–0.60 and 0.39–0.53, respectively) validity. Conclusions : Both ALA and ALA-C demonstrated excellent reliability and good validity. Further research is warranted to examine use by more practicing clinicians and with more participants of varying degrees of aphasia severity to enable additional investigation of its psychometric properties.